ORBIT II sub‐analysis: Impact of impaired renal function following treatment of severely calcified coronary lesions with the Orbital Atherectomy System. Issue 5 (27th August 2016) - Lee, Michael S.; Lee, Arthur C.; Shlofmitz, Richard A.; Martinsen, Brad J.; Hargus, Nick J.; Elder, Mahir D.; Généreux, Philippe; Chambers, Jeffrey W.
Abstract : Objectives: To investigate the safety and efficacy of the coronary Orbital Atherectomy System (OAS) to prepare severely calcified lesions for stent deployment in patients grouped by renal function. Background: Percutaneous coronary intervention (PCI) of severely calcified lesions is associated with increased rates of major adverse cardiac events (MACE), including death, myocardial infarction (MI), and target vessel revascularization (TVR) compared with PCI of non‐calcified vessels. Patients with chronic kidney disease (CKD) are at increased risk for MACE after PCI. The impact of CKD on coronary orbital atherectomy treatment has not been well characterized. Methods: ORBIT II was a prospective, multicenter trial in the U.S., which enrolled 443 patients with severely calcified coronary lesions. The MACE rate was defined as a composite of cardiac death, MI, and target vessel revascularization. Results: Of the 441 patients enrolled with known estimated glomerular filtration rate (eGFR) values at baseline, 333 (75.5%) patients had eGFR < 90 ml/min/1.73 m 2 and 108 patients had eGFR ≥ 90 ml/min/1.73 m 2 . The mean eGFR at baseline in the eGFR < 90 ml/min/1.73 m 2 and eGFR ≥ 90 ml/min/1.73 m 2 groups was 65.0 ± 0.9 ml/min/1.73 m 2 and 109.1 ± 2.0 ml/min/1.73 m 2, respectively. Freedom from MACE was lower in the eGFR < 90 ml/min/1.73 m 2 group at 30 days (87.4% vs. 96.3%, P  = 0.02) and 1‐year (80.6% vs. 90.7%, P  = 0.02). Conclusions: Patients with renal impairment had a higher MACE rate through one year follow‐up due to a higher rate of periprocedural MI. Interestingly, the rates of cardiac death and revascularization through 1‐year were similar in patients with eGFR < 90 ml/min/1.73 m 2 and eGFR ≥ 90 ml/min/1.73 m 2 . Future studies are needed to identify the ideal revascularization strategy for patients with renal impairment and severely calcified coronary lesions. © 2016 Wiley Periodicals, Inc.